Selectivity Changes during Activation of Mutant Shaker Potassium Channels - Zheng, Jie (The Rockefeller University Press, 1997)
Mutations of the pore-region residue T442 in Shaker channels result in large effects on channel kinetics. We studied mutations at this position in the backgrounds of NH(2)-terminal–truncated Shaker H4 and a Shaker -NGK2 chimeric channel having high conductance (Lopez, G.A., Y.N. Jan, and L.Y. Jan. 1994. Nature (Lond.). 367: 179–182). While mutations of T442 to C, D, H, V, or Y resulted in undetectable expression in Xenopus oocytes, S and G mutants yielded functional channels having deactivation time constants and channel open times two to three orders of magnitude longer than those of the parental channel. Activation time courses at depolarized potentials were unaffected by the mutations, as were first-latency distributions in the T442S chimeric channel. The mutant channels show two subconductance levels, 37 and 70% of full conductance. From single-channel analysis, we concluded that channels always pass through the larger subconductance state on the way to and from the open state. The smaller subconductance state is traversed in ∼40% of activation time courses. These states apparently represent kinetic intermediates in channel gating having voltage-dependent transitions with apparent charge movements of ∼1.6 e(0). The fully open T442S chimeric channel has the conductance sequence Rb(+) > NH(4) (+) > K(+). The opposite conductance sequence, K(+) > NH(4) (+) > Rb(+), is observed in each of the subconductance states, with the smaller subconductance state discriminating most strongly against Rb(+).